Differences in preferences for office attributes in hybrid working: Office versus Flexible Workdays - Tuzcuoglu, Deniz; Appel-Meulenbroek, Rianne; Borgers, Aloys; Arentze, Theo; Sungur, Asli (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2025)
Hybrid work has become increasingly common, yet it remains unclear how employees prefer office environments that accommodate the dynamics of hybrid work. In particular, there is a limited understanding of whether preferences for office environments differ between Office Workdays when employees are expected to work from the office and Flexible Workdays when they can choose to work at the office or remotely. This study examines workplace choice decisions to identify within-person differences in preferences for seven office attributes between these two workday types. A stated choice experiment was conducted with 1812 employees from three Dutch municipalities and analysed using three multinomial logit models. The results reveal significant differences in office preferences between the two workday types. Only preferences for technology type remain consistent across both workday types, while significant differences in preferences emerged for kitchenette type, events, other occupants, workspace type, aesthetics, and workplace access. For example, a kitchenette with a sitting and gaming area enhanced the office appeal only on Flexible Workdays, while kitchenettes with a sitting area or standing tables increased the office attractiveness only on Office Workdays. Although employees generally have neutral or weaker preferences for office attributes on Flexible Workdays than on Office Workdays, they show relatively stronger preferences for office-events on Flexible Workdays. Organisations should consider these differences in preferences when designing office environments to enhance workplace experiences on both workday types in hybrid work settings.
Keywords: Hybrid working; Preferences; Workplace choice behaviour; Office design; PERCEIVED PRODUCTIVITY; SATISFACTION; WORKPLACE; WORKSPACE; ENVIRONMENT; SUPPORT; COLOR; EMPLOYEES; IMPACTS; MOOD; Environmental Sciences & Ecology; Psychology